2014
DOI: 10.7150/ijbs.9028
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Quenching Mediated Approaches for Control of Membrane Biofouling

Abstract: Membrane biofouling is widely acknowledged as the most frequent adverse event in wastewater treatment systems resulting in significant loss of treatment efficiency and economy. Different strategies including physical cleaning and use of antimicrobial chemicals or antibiotics have been tried for reducing membrane biofouling. Such traditional practices are aimed to eradicate biofilms or kill the bacteria involved, but the greater efficacy in membrane performance would be achieved by inhibiting biofouling without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
77
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(87 citation statements)
references
References 225 publications
0
77
0
2
Order By: Relevance
“…Moreover, the inhibition of QS systems has other important applications, like the control of membrane fouling (Lade et al 2014). Two main strategies have been explored to interfere with AHLmediated QS systems: the use of inhibitory substances that block signal reception and the enzymatic degradation of signals.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the inhibition of QS systems has other important applications, like the control of membrane fouling (Lade et al 2014). Two main strategies have been explored to interfere with AHLmediated QS systems: the use of inhibitory substances that block signal reception and the enzymatic degradation of signals.…”
Section: Introductionmentioning
confidence: 99%
“…Several advantages of MBR over activated sludge processes have been observed, such as lower sludge generation, higher effluent water quality with the near absence of pathogens, and a lower footprint required for bioreactor construction (Cosenza et al 2013). However, one of the major problems identified for the application of MBR to full-scale operation is the membrane pore clogging process known as biofouling (Lade et al 2013;Gao et al 2014;Lade et al 2014).…”
mentioning
confidence: 99%
“…It has been observed that quorum sensing is associated with the formation of a biofouling layer on the membrane surface in a membrane bioreactor (MBR) wastewater treatment system (7). The use of AHL-degrading enzymes has been investigated as an approach to controlling membrane biofouling in wastewater treatment systems (9).…”
mentioning
confidence: 99%